2009
DOI: 10.1007/s00383-009-2357-3
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal survival of prenatally diagnosed exomphalos

Abstract: Antenatal diagnosis of exomphalos is 96% sensitive. Severe karyotypic and structural abnormalities were present in all intra-uterine and early postnatal deaths. Overall survival to discharge was 28%. Both minor and isolated exomphalos carried a good prognosis. Isolated exomphalos was a better prognostic factor than severity of the exomphalos itself. Ruptured giant exomphalos were associated with a poorer outcome especially in premature babies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 9 publications
0
12
0
5
Order By: Relevance
“…First, we did not directly study the association between gene polymorphisms and the plasma ACE and AGT levels. However, the ACE DD genotype has been clearly associated with the higher plasma and tissue levels of ACE [17, 40, 41]. In addition, Jeunemaitre et al [18] have found a greater association between the AGT TT genotype and higher plasma AGT levels, compared to that of the AGT MM genotype.…”
Section: Discussionmentioning
confidence: 99%
“…First, we did not directly study the association between gene polymorphisms and the plasma ACE and AGT levels. However, the ACE DD genotype has been clearly associated with the higher plasma and tissue levels of ACE [17, 40, 41]. In addition, Jeunemaitre et al [18] have found a greater association between the AGT TT genotype and higher plasma AGT levels, compared to that of the AGT MM genotype.…”
Section: Discussionmentioning
confidence: 99%
“…As Patel et al [4] reported, the existence of associated anomalies affects prognosis more than the severity of the omphalocele itself, and antenatal evaluation of the associated anomalies is useful to enable appropriate care immediately after birth. In this study, chromosomal aneuploidy was observed in 36.8% of cases, and associated anomalies, including chromosomal aberrations, were detected in 76.3%; these findings are similar to those in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of big or giant omphalocele published in previous studies is heterogeneous and include presence of the liver in the omphalocele sac [11], more than 75% of the liver in the omphalocele sac [12] or the entire liver in the omphalocele sac [10]. Therefore, comparison of results across different studies that have evaluated prognosis in cases diagnosed antenatally is difficult.…”
Section: Introductionmentioning
confidence: 98%
“…When omphalocele is an isolated finding, survival rates following surgical repair are over 90% [8,9,10]. Nevertheless, increased postnatal morbidity and surgical pitfalls are related to the size of the herniated content and giant defects, which include the liver [11].…”
Section: Introductionmentioning
confidence: 99%